Hetero-oligomerization of C2 domains of phospholipase C-related but catalytically inactive protein and synaptotagmin-1. (January 2015) - Wang, DaGuang; Takeuchi, Hiroshi; Gao, Jing; Zhang, Zhao; Hirata, Masato
Abstract: The C2 domain is a protein module often found in molecules that regulate exocytosis. C2 domains mediate interactions between the parental molecule and Ca 2+, phospholipids, and proteins. Although various molecules have been shown to interact with several C2 domains, no interactions between the C2 domains from different molecules have yet been reported. In the present study, we identified direct interactions between the C2 domain of PRIP (phospholipase C-related but catalytically inactive protein) and the C2 domains of other molecules. Among the C2 domains examined, those of synaptotagmin-1 (Syt1-C2A and Syt1-C2B) and phospholipase C δ-1 bound to the C2 domain of PRIP. We investigated the interactions between the C2 domain of PRIP (PRIP-C2) with Syt1-C2A and Syt1-C2B, and the mode of binding of each was Ca 2+ -dependent and -independent, respectively. We further demonstrated that the Ca 2+ dependence of the interaction between PRIP-C2 and Syt1-C2A was attributed to Ca 2+ binding with Syt1-C2A, but not PRIP-C2, using a series of mutants prepared from both C2 domains. We previously reported that the interaction between PRIP-C2 and the membrane fusion machinery suggested a critical role for PRIP in exocytosis; therefore, the results of the present study further support the importance of PRIP-C2 in the inhibitory function of PRIP in regulating exocytosis.